2000
DOI: 10.1001/archfami.9.10.979
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pseudoephedrine Plus Acetaminophen for Treatment of Symptoms Attributed to the Paranasal Sinuses Associated With the Common Cold

Abstract: Our results suggest that pseudoephedrine plus acetaminophen is effective for relief of symptoms attributable to the paranasal sinuses that may develop early in the course of a cold. Arch Fam Med. 2000;9:979-985

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…No animal or clinical data validating the use of the FDC for treatment of cough and common cold was available for majority of the formulations. Results of studies of only 12 FDCs marketed in 2007 were available [19][20][21][22][23][24][25][26][27][28][29][30]. Because our objective was to determine the availability of animal or human trial data on these FDCs and not assessment of their efficacy, we have not analyzed the results of these trials.…”
Section: Discussionmentioning
confidence: 99%
“…No animal or clinical data validating the use of the FDC for treatment of cough and common cold was available for majority of the formulations. Results of studies of only 12 FDCs marketed in 2007 were available [19][20][21][22][23][24][25][26][27][28][29][30]. Because our objective was to determine the availability of animal or human trial data on these FDCs and not assessment of their efficacy, we have not analyzed the results of these trials.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In one study, pseudoephedrine was shown to decrease rhinorrhea during the common cold, presumably related to its vasoconstrictor properties. 21 In the same study, pseudoephedrine had no effect on the symptom of sneezing. In clinical studies using pseudoephedrine, some efficacy in controlling sneezing, rhinorrhea, and itch has been reported.…”
Section: Commentmentioning
confidence: 87%
“…Furthermore, it should be mentioned that this concept would also explain why medications addressing nasal mucosa are effective in reducing headache in ARS (i.e. intranasal corticosteroids ( 12 ), decongestants ( 13 )). Finally, it should be underlined that our study does not confirm causality between ARS and headache despite the above described rationale.…”
Section: Discussionmentioning
confidence: 99%